Effects of a 12-week high-α-linolenic acid intervention on EPA and DHA concentrations in red blood cells and plasma oxylipin pattern in subjects with a low EPA and DHA status. Issue 3 (20th February 2018) - Greupner, Theresa; Kutzner, Laura; Nolte, Fabian; Strangmann, Alena; Kohrs, Heike; Hahn, Andreas; Schebb, Nils Helge; Schuchardt, Jan Philipp
Abstract : The essential omega-3 fatty acid alpha-linolenic acid (ALA, 18:3n3) can be converted into EPA and DHA. Abstract : The essential omega-3 fatty acid alpha-linolenic acid (ALA, 18:3n3) can be converted into EPA and DHA. The aim of the present study was to determine the effect of a high-ALA diet on EPA and DHA levels in red blood cells (RBCs) and their oxylipins in the plasma of subjects with a low EPA and DHA status. Fatty acid concentrations [μg mL −1 ] and relative amounts [% of total fatty acids] in the RBCs of 19 healthy men (mean age 26.4 ± 4.6 years) were analyzed by means of GC-FID. Free plasma oxylipin concentrations were determined by LC-MS based targeted metabolomics. Samples were collected and analyzed at baseline (week 0) and after 1 (week 1), 3 (week 3), 6 (week 6), and 12 (week 12) weeks of high dietary ALA intake (14.0 ± 0.45 g day −1 ). ALA concentrations significantly ( p < 0.001) increased from 1.44 ± 0.10 (week 0) to 4.65 ± 0.22 (week 1), 5.47 ± 0.23 (week 3), 6.25 ± 0.24 (week 6), and 5.80 ± 0.28 (week 12) μg mL −1 . EPA concentrations increased from 6.13 ± 0.51 (week 0) to 7.33 ± 0.33 (week 1), 8.38 ± 0.42 ( p = 0.021, week 3), 10.9 ± 0.67 ( p < 0.001, week 6), and 11.0 ± 0.64 ( p < 0.001, week 12) μg mL −1 . DHA concentrations unexpectedly decreased from 41.0 ± 1.93 (week 0) to 37.0 ± 1.32 (week 1), 36.1 ± 1.37 (week 3), 35.1 ± 1.06 ( p = 0.010, week 6), and 30.4 ± 1.09 ( p < 0.001, week 12) μg mL −1 . Relative ΣEPA + DHA amounts were unchanged during the intervention (week 0: 4.63 ± 0.19, week 1: 4.67 ± 0.16, week 3: 4.61 ± 0.13, week 6: 4.73 ± 0.15, week 12: 4.52 ± 0.11). ALA- and EPA-derived hydroxy- and dihydroxy-PUFA increased similarly to their PUFA precursors, although in the case of ALA-derived oxylipins, the concentrations increased less rapidly and to a lesser extent compared to the concentrations of their precursor FA. LA-derived oxylipins remained unchanged and arachidonic acid and DHA oxylipin concentrations were not significantly changed. Our results confirm that the intake of ALA is not a sufficient source for the increase of EPA + DHA in subjects on a Western diet. Specifically, a high-ALA diet results in increased EPA and declined DHA concentrations. However, the changes effectively balance each other out so that ΣEPA + DHA in RBCs – which is an established marker for health protective effects of omega-3-PUFA – remains constant. The PUFA levels in RBCs reflect the concentration and its changes in plasma hydroxy- and dihydroxy-PUFA concentrations for ALA and EPA.